A prospective study on sex differences in functional capacity, quality of life and prognosis in patients with heart failure. Issue 26 (30th June 2022) - Ma, Yiming; Shi, Yunke; Ma, Wenfang; Yang, Dan; Hu, Zhao; Wang, Mingqiang; Cao, Xingyu; Zhang, Chaoyue; Luo, Xiang; He, Shulin; Zhang, Min; Duan, Yong; et al.
Abstract : Background: Due to the lack of evidence and inconsistency of sex differences in Heart failure (HF) in the Chinese population, this study aimed to compare sex differences in functional capacity and quality of life (QoL) between women and men after standard HF medications therapies, and analyze whether sex differences were associated with the composite endpoints of all-cause mortality or HF-related hospitalization and cardiac event-free survival rate in Chinese patients with HF. Methods: This was a 1-year longitudinal study. Participants included patients with HF from March 2017 to December 2018. At baseline and followed up at 1, 6, and 12 months later, functional capacity was assessed by 6-minute walk testing (6MWT), QoL was measured with the Kansas City Cardiomyopathy Questionnaire (KCCQ) and EuroQoL five dimensions (EQ-5D). The Cox proportional hazards model and Kaplan-Meier curves were used to determine sex differences in subsequent outcomes. The Cox proportional hazards model was used to identify the risk factors for composite endpoints. Kaplan-Meier curves were used to compare survival. Results: All patients were assigned to either men group (n = 94) or women group (n = 60). Longitudinal follow-ups showed a continuously increasing in 6MWT, Kansas City Cardiomyopathy Questionnaire overall score, EQ-5D visual analogue scale, and EQ-5D Index score in both groups (all P < 0.001); however, women reported a lower level of all parameters at the 1, 6, and 12 months follow-ups (all P < 0.05). In addition, women had a higher risk of all-cause mortality or HF-related hospitalization and a lower cardiac event-free survival rate than men (log-rank test, P = 0.027). Conclusion: Women reported worse functional capacity, QoL, and prognosis than men in a sample of Chinese patients with HF. Our findings highlight the importance of paying attention to sex differences in HF.